Publication Trend on Insurance Efficiency Studies - Annisa Kartika Ocktavia; Siti Salmah (SMART Insight, 2023)
This study aims to determine the map of the development of research on the theme of insurance efficiency which is published in journals equipped with digital object identifiers. The research was conducted in August 2023. The data analyzed were 336 research journals related to insurance efficiency published from 1992 to 2023. During this period, the most research on insurance efficiency occurred in 2022 with 40 publications. The data is then processed and analyzed using the VOSviewer application program to determine the bibliometric mapping for the development of insurance efficiency research. The results show that cost efficiency, economy, evidence, firm, insurance firm, insurance sector, market, risk, originality value, relationship and stage data envelopment are the most widely used topics. The research development map for this theme is divided into 5 clusters. Cluster 1 consists of 11 topics, cluster 2 consists of 9 topics, cluster 3 consists of 9 topics cluster 4 consists of 5 topics and cluster 5 consists of 5 topics.